THE EFFECTIVENESS OF SOCIO HISTORICAL TOPICS IN UNDERSTANDING THE WORLDVIEW OF PRIMARY SCHOOL STUDENTS - Jumayeva G. T.; M. K. Sattarova (Scholars Digest Publishing, 2024)
This article explores ways to further stimulate and enhance interest in reading and learning activities among modern students, to form creative and information-related intellectual mechanisms, and to improve their thinking based on national culture.
Keywords: Primary education, spiritual and moral, literary and aesthetic education, interest, advanced pedagogical technology, teacher and student activities.